2020
DOI: 10.31711/giw.v7.pp1-27
|View full text |Cite
|
Sign up to set email alerts
|

Fallout tuffs in the Eocene Duchesne River Formation, northeastern Utah—ages, compositions, and likely source

Abstract: Thin fallout tuffs are common in the terrestrial deposits of the Eocene Duchesne River Formation on the flanks of the Uinta Mountains of eastern Utah. Their ages and compositions provide new insight into the tectonic events and magmatic history of the western Cordillera and provide important constraints on the Cenozoic land mammal chronology. Whole-rock compositions of the volcanic ash show that they underwent post-emplacement argillic alteration, typical of a wetland/floodplain depositional setting. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Differential uplift continued episodically into the Oligocene. For example, Jensen et al (2020) concluded that there were two late episodes of relative uplift in the Uinta Mountains-one at ca. 39 Ma to form the clastic sediment of the Duchesne River Formation and another at ca.…”
Section: ■ Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential uplift continued episodically into the Oligocene. For example, Jensen et al (2020) concluded that there were two late episodes of relative uplift in the Uinta Mountains-one at ca. 39 Ma to form the clastic sediment of the Duchesne River Formation and another at ca.…”
Section: ■ Geologic Settingmentioning
confidence: 99%
“…In addition, Kowallis et al (1995) inferred that the northeast strike of middle Cenozoic dikes and microcracks in plutonic quartz is probably related to northeast-directed compression rather than northwest-southeast extension. Another structural argument against extension at this time lies in the observations of Jensen et al (2020) that contractional deformation in the Uinta arch continued until ca. 30 Ma when strata of the Duchesne River Formation were folded and the erosional detritus formed the Bishop Conglomerate.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Differential uplift continued episodically into the Oligocene. For example, Jensen et al (2020) concluded that there were two late episodes of relative uplift in the Uinta Mountains-one at ca. 39 Ma to form the clastic sediment of the Duchesne River Formation and another at ca.…”
Section: ■ Geologic Settingmentioning
confidence: 99%
“…In addition, Kowallis et al (1995) inferred that the northeast strike of middle Cenozoic dikes and microcracks in plutonic quartz is probably related to northeast-directed compression rather than northwest-southeast extension. Another structural argument against extension at this time lies in the observations of Jensen et al (2020) that contractional deformation in the Uinta arch continued until ca. 30 Ma when strata of the Duchesne River Formation were folded and the erosional detritus formed the Bishop Conglomerate.…”
Section: Tectonic Settingmentioning
confidence: 99%